Effect of White Noise on the Sleep of Elderly Patients Hospitalized in Coronary Care Units - Pouya Farokhnezhad Afshar; Hosein Zahednezhad; Mehdi Ajri Khamesloo; Reza Ghanei Gheshlagh; Reza Fathi (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Sleep disorders are prevalent among elderly patients admitted to coronary care units (CCUs). Moreover, the sleep disorders intensify with age-related changes. Thus, this study aimed to determine the effect of white noise on the sleep of elderly patients admitted to CCUs. Methods & Materials: This quasi-experimental research included 40 patients who were admitted to CCU. The sampling was done by convenience sampling method and by following the inclusion criteria. In this study, sleep duration and sleep latency of the patients were measured on the first day of hospital admission and 1 week after hospitalization in CCU in both the control group and experimental group. The experimental group received “white noise” (ocean sound) for 2 hours each day before bedtime for 1 week while the control group received no such noise. The obtained data were analyzed by statistical tests (Chi-squared test, independent t-test, and paired t-test) through SPSS, version 18. Results: The mean (SD) age of the participants was 68.75(6.19) years in the control group and 67.05(5.15) years in the experimental group. Most participants were men (57.5%). In addition, most of them were hospitalized with acute coronary syndrome (80%), and 65% had a history of hospitalization. The mean (SD) sleep duration in the control group was 7.16(0.86) hours before the intervention, which decreased to 4.69±0.56 hours after the study. The mean (SD) sleep latency in the control group increased from 20±5.4 minutes to 28±5.4 minutes after the intervention, which shows a significant reduction in sleep quantity after hospitalization (P<0.001). The mean (SD) sleep duration of the experimental group did not show any significant difference with that of the control group [6.75(0.91) h) (P=0.146). Furthermore, after the study, the mean (SD) of sleep duration in the experimental group did not show any significant reduction [7.04(0.91) h) (P=0.12). The sleep latency duration of the older people in the control group decreased from 19 (5.4) minutes to 17 (4.2) minutes (P=0.17). The comparison of sleep duration and sleep latency of both groups after the study indicated a significant difference between 2 groups (P<0.001 for both variables). Conclusion: Our results showed that white noise did not significantly change the sleep quality of old patients; however, it prevented the decrease in sleep duration and the increase in sleep latency duration. White noise with regard to its effects on increasing auditory stimulation threshold, its sleep induction, and suitable cost-effectiveness, can be used for some old patients hospitalized in CCUs.